An empirical platform for behavioural modelling using serious games - Daniel dos Santos Teixeira (2016)
Each day serious games are becoming more relevant and taken seriously by responsible institutions. Although the overall society is still not truly familiar with this concept, there are great benefits that can be achieved with this games. As said in [OPO+15], applications have a wide range of domains, naturally including social simulation, where data collection of player attitudes can be later used for statistical analysis, and behavioral pattern recognition. This makes them an important tool to both educational and social intervention. But how can we use this concept with behavior elicitation? How can we make a game, with mechanics that allow decision points and use this to both collect data and simulate emergency situations? In [RAR+12], we learn that Video games present some characteristics that make them helpful as a resource. As sentiments like enjoyment and fulfillment are felt, users are more likely to stay motivated while doing their tasks. Also it is much easier for the human being to assimilate mechanics or techniques rather than theoretic knowledge. The main goal of this master thesis is to make a game platform for research and development in the field of behavior modeling. The data collection needed can be done using the game and its mechanics, and then improve the game to make it more realistic and immersive. Being a simulation of emergency situations the realism helps the elicitation, assimilation and persuasion wanted for the project. The solution must be adaptive to the need of the subject. There must be alternative scenarios and mechanics to chose from. This way, not only the game can reach more kinds of people and situations, but also, represent more accurately their required need.